Constitutionality of Parliamentary Threshold for 2029 General Election After Constitutional Court Decision No 116/PUU-XXI/2023 - Zul Adli; Edi Rosman; Beni Firdaus; Dahyul Daipon; Ahmad Alfarisi (Hakamain: Journal of Sharia and Law Studies, 2025)
This study aims to analyze the constitutionality of the parliamentary threshold for the 2029 general election following Constitutional Court Decision No. 116/PUU-XXI/2023. The research applies a normative juridical method with statutory and conceptual approaches, focusing on legal norms, constitutional principles, and relevant court decisions. Data are collected through literature review, including legislation, constitutional court rulings, and academic writings, and are analyzed qualitatively. The findings reveal that the parliamentary threshold remains constitutionally valid as a mechanism to simplify the party system and support the effectiveness of the presidential system. However, its implementation must adhere to democratic principles, particularly popular sovereignty, equality of political rights, and fair representation. The Constitutional Court’s decision reflects a model of conditional constitutionality, requiring that any threshold policy be rational, proportional, and not excessively limit political participation. This study concludes that future regulation of the parliamentary threshold must carefully balance electoral system efficiency with the protection of citizens’ constitutional rights. The academic contribution of this research lies in offering a comprehensive interpretation of constitutional law in the field of electoral governance, especially in linking democratic theory with constitutional adjudication. Additionally, this study provides insights into the broader implications of judicial review decisions on legislative policy-making and electoral reform in Indonesia.